ESL Supplement (green) : level 2. (Columbus, Ohio : SRA/McGraw-Hill, 2000)
Students who are learning to speak English as a Second Language (ESL) may need extra help with the Open Court Reading lessons. The ESL Supplement is a resource the teachers can use in providing extra help with English vocabulary and sentence structure.
Keywords: Reading--Study and Teaching; Writing--Study and Teaching; English language--Study and Teaching